An evaluation of data completeness of VGI through geometric similarity assessment. (2nd October 2018) - Chehreghan, Alireza; Ali Abbaspour, Rahim
ABSTRACT: Evaluation of the quality of volunteered geographic information (VGI) has been the subject of a plethora of research in recent years as an imperative issues. In this paper, the corresponding objects between data sets of OpenStreetMap, as one of the well-known VGI projects, and the reference data sets are identified based on an automatic linear object matching method. Moreover, to identify more corresponding objects in two data sets and measuring the completeness more accurately, geometric properties are used. The results showed that 92% of the objects of the OSM data set matched to the reference data set and the total length of the matched objects was 87% of the total length of the objects. The corresponding objects in two data sets have average of 0.86° of spatial similarity. By examining the objects of the OSM data set from 2013 to 2017, a rise of 87.2% detected in individuals' participation in creating the objects and the average spatial similarity degree also underwent an improvement of 0.15.